A Red‐Emissive Sextuple Hydrogen‐Bonding Self‐Assembly Molecular Duplex Bearing Perylene Diimide Fluorophores for Warm‐White Organic Light‐Emitting Diode Application. Issue 4 (3rd February 2016) - Zeng, Hui; Huang, Qingyu; Liu, Jingjing; Huang, Yan; Zhou, Jie; Zhao, Suling; Lu, Zhiyun
Abstract: A novel sextuple hydrogen‐bonding (HB) self‐assembly molecular duplex bearing red‐emitting perylene diimide (PDI) fluorophores, namelyPDIHB, was synthesized, and its molecular structure was confirmed by 1 H NMR, 13 C NMR, TOF‐MS and 2D NMR. Compared with the small molecular reference compoundPDI, PDIHB shows one time enhanced fluorescence efficiency in solid state (4.1% vs. 2.1%). More importantly, the presence of bulky HB oligoamide strands inPDIHB could trigger effective spatial separation between guest and host fluorophores in thin solid film state, hence inefficient energy transfer occurs between the blue‐emitting host2TPhNIHB and red guestPDIHB in the 2 wt% guest/host blending film. As a result, a solution‐processed organic light‐emitting diode (OLED) with quite simple device structure of ITO/PEDOT:PSS (40 nm)/PVK (40 nm)/PDIHB (2 wt%):2TPhNIHB (50 nm)/LiF (0.8 nm)/Al (100 nm) could emit bias‐independent warm‐white electroluminescence with stable Commission Internationale de L'Eclairage coordinates of (0.42, 0.33), and the maximum brightness and current efficiency of this device are 260 cd·m −2 and 0.49 cd·A −1, respectively. All these results indicated that HB self‐assembly supramolecular fluorophores could act as prospective materials for white OLED application. Abstract : A red‐emissive hydrogen‐bonding self‐assembly duplex was synthesized. The bulky self‐assembly oligoamide strands are advantageous to the spatial isolation between the host and guest materials, hence trigger an inefficient energy transfer process. Based on it, a solution‐processed warm‐white OLED with simple device structure was acquired.